Avaliação in vitro e in vivo de dentifrício contendo hidrocolóide como sistema de liberação controlada de flúor - Alves, Vanessa Feitosa (2016)
Introduction: Hydrocolloids are natural products used as controlled drug delivery system. The addition of hydrocolloid (tara gum) associated with fluoride (F) can be a promising strategy for increasing the substantivity of fluoride dentifrices. Aim: To evaluate experimental dentifrices containing hydrocolloid (tara gum) as a controlled delivery system of F for remineralizing initial caries lesion in vitro and to investigate in vivo retention hability of F in biofilm and saliva after its use. Material and Methods: The dentifrice groups used in this study were: 100-TGF (All NaF associated to tara gum); 50-TGF (50% NaF associate to tara gum + 50% free NaF); CD (convencional dentifrice with NaF); TG (dentifrice with tara gum and without F); placebo (negative control, without F and without tara gum). All fluoride dentifrices had 1100 mg/mL F. For the in vitro model, 75 blocks of human teeth enamel were allocated in five groups. First, it was produced enamel demineralization lesion follow the pH cycling model for five days at 37ºC. The treatment was performed with the slurry of the dentifrice under agitation (twice a day, 1 minute, 37ºC). The blocks were submitted to surface microhardness mensuraments from which it was calculated the remineralization percentual (%SMHR). The data were analyzed by ANOVA test followed by Tukey test. The in vivo model was a crossover randomized triple-blind trial with 18 individuals resident in João Pessoa (city without water fluoridation). After a week use, samples of biofilm and stimulated saliva were collected. The collection times were 1 and 12 hours (h) after the last brushing for the biofilm, and 0, 1, 5, 10, 15, 20, 30, 45, 60 minutes and 12h for the saliva. The F concentrations in these samples were analyzed by specific electrode through the acid-hexamethyldisiloxane (HMDS) diffusion method. The data were analyzed by the repeated measures ANOVA followed by Bonferroni test. Area under curve (AUC) after 1h of brushing was calculated for saliva data. Results: The %SMHR observed were: CD (3.49) > CN (0.65) > 50-TGF (0.26) > 100-TGF (-1.59) > TG (-5.48). No statistical difference was observed except for TG versus CD and CN (p<0.05). Biofilm and salivary F levels were highter after the use of fluoride dentifrices when compared to values of placebo and TG. No statistical difference between F retention on biofilm at 1h and 12h after the brushing for the 100-TGF, placebo and TG (p>0.05) was found. The highest AUC values were for 50-TGF, 100-TGF and CD, respectively. Conclusion: The experimental dentifrices containing tara gum did not show additional effect on F release using this in vitro model. The in vivo outcomes indicates the efficacy of the dentifrice containing tara gum as a controlled delivery system of F in promoting F retention on the oral cavity even after 12 hours of brushing.